Classroom Management as Virtual World for Creating Professional Teaching Environment - Pastraporn Thipayasothorn; Amornchai Chaichana; Aueamaumporn Phetsinchorn (My University, 2024)
Research and innovation for community or local development, aims at providing the individuals with a high quality of life and enhancing capabilities for competition through collaborative efforts of stakeholders, including beneficiaries in the area, especially the academic sector of which powerful educational institutions in the central and metropolitan areas of Thailand. Innovation in vocational education management through online teaching environments intends to have educational innovations in the central and metropolitan areas as a mechanism and process of educational reform that can manage online teaching in line with the local context. This involves flexible and adaptable management that eliminates the need for travel and reduces consumption of resources. This is achieved by research objective of 1) developing innovations in vocational education management through online teaching environments to enhance educational efficiency, 2) reducing educational quality disparities by designing virtual reality training centers for professional skill development, with a case study in the field of art and design, and 3) developing mechanisms for collaborative education management in the community, through the design and use of application programs to create a professional teaching environment. Therefore, this research and innovation in vocational education management in the central region of Thailand through online teaching environments can enhance self-directed learning. This involves designing and developing learning technology, creating a virtual world to establish a professional teaching environment, and innovating learning application programs from 400 sampling. The education system in this changing crisis has a responsibility to stimulate and revive the grassroots economy after the crisis. This emphasizes the crucial role of education as a continuous tool in building economic and social resilience later.
Keywords: Educational Innovations and Challenges; Innovative Educational Technologies; Educational Methods and Teacher Development